Efficiency of repair of an abasic site within DNA clustered damage sites by mammalian cell nuclear extracts. - Lomax, M; Cunniffe, S; O'Neill, P (2004)
Ionizing radiation induces clustered DNA damage sites which have been shown to challenge the repair mechanism(s) of the cell. Evidence demonstrating that base excision repair is compromised during the repair of an abasic (AP) site present within a clustered damage site is presented. Simple bistranded clustered damage sites, comprised of either an AP-site and 8-oxoG or two AP-sites, one or five bases 3' or 5' to each other, were synthesized in oligonucleotides, and repair was carried out in xrs5 nuclear extracts. The rate of repair of an AP-site when present opposite 8-oxoG is reduced by up to 2-fold relative to that when an AP-site is present as an isolated lesion. The mechanism of repair of the AP-site shows asymmetry, depending on its position relative to 8-oxoG on the opposite strand. The AP-site is rejoined by short-patch base excision repair when the lesions are 5' to each other, whereas when the lesions are 3' to one another, rejoining of the AP-site occurs by both long-patch and short-patch repair processes. The major stalling of repair occurs at the DNA ligase step. 8-OxoG and an AP-site present within a cluster are processed sequentially, limiting the formation of double-strand breaks to <4%. In contrast, when two AP-sites are contained within the clustered DNA damage site, both AP-sites are incised simultaneously, giving rise to double-strand breaks. This study provides new insight into understanding the processes that lead to the biological consequences of radiation-induced DNA damage and ultimately tumorigenesis.